Passive acoustic survey reveals the abundance of a low-density predator and its dependency on mature forests - Baroni Daniele; Hanzelka Jan; Raimondi Teresa; Gamba Marco; Brommer Jon E; Laaksonen Toni (SPRINGER, 2025)
Context
Even though habitat use is essential information for conservation management strategies, studying it in elusive and scarce forest species has proven challenging. Passive acoustic monitoring allows collecting accurate presence-absence data even for species that typically exhibit low detectability. It further provides tools for long-term and cost-effective biodiversity monitoring, and may also be used to infer population estimates at the landscape level.
Objectives
We aimed to demonstrate the application of passive acoustic monitoring to the problem of detecting elusive species, especially in forests, using the Eurasian pygmy owl as a model species. We explored its habitat selection, and estimated occupancy and density at the landscape level in the managed boreal forest.
Methods
We conducted a wide-scale autonomous recording units (ARUs) survey, involving 292 sites in a single season, in a study area covering approx. 370 km(2) in south-western Finland. We clustered the detections into territories of males to infer population size by also taking into account the size of home ranges derived from GPS-tags data. Since we were simultaneously monitoring the occupancy of a network of nest boxes and previously estimated the abundance of natural cavities, we could also estimate the proportion of pygmy owls nesting in natural cavities.
Results
Increasing availability of mature forests was consistently the most critical habitat variable both for calling and nesting sites, increasing occupancy probability of the pygmy owls in a landscape dominated by managed forests. The proportion of sites showing occupancy by the pygmy owls was 20.9%, corresponding to an estimate of ca. Six territorial males/100 km(2).
Conclusion
Our results confirmed that the pygmy owl can be considered a species of mature and old forests, and we provide the first data-based estimate of the total density of territorial males of this species. Passive acoustic monitoring proved to be an efficient method in detecting the presence of pygmy owls, and may overcome weaknesses of other methods, such as nest box surveys, in order to quantify population numbers.